ADOPSI KONSERVASI SEBAGAI BENTUK INVESTASI USAHA JANGKA PANJANG (Studi Kasus Usahatani Kentang Lahan Kering Dataran Tinggi Pangalengan) - Ratna Katharina (School of Business, Bogor Agricultural University (SB-IPB), 2007)
The main objective of the study is to proof that the adoption of conservation is a decision according with the purpose of firm to increase its profit. To apply a good corporate governance, conservation is not just a firm’s burden but it’s part of the firm’s effort to maintain the sustainability of its business. The study was carried out in Pangalengan subdistrict, Bandung. The data for study analysis is collected from cross-sectional data of farm households. Respondent of 180 farmers ( 15 % of population) was drawn randomly from 13 villages. The respondent amount of each village was drawn proportionally. Financial Analysis, Benefit Cost Analysis and SCUAF model were applied to quantify farm income, productivity, and soil erosion of conservation farming practices in the short and long run. The findings of the study highlighted a significant difference in farm income, productivity, and soil erosion between farming practices with and without conservation measures. In the long run, adoption of conservation yield a higher net present value (NPV) and productivity, and they also conserve the soil.